Economic Activity of Farms Against Farms Countries of the European Union - Brelik, Agnieszka (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The development of an economic activity has been considered as a driving force for economic development, creating a chance to remove the rural population outside the agricultural sector. This article presents an analysis of the development of non-agricultural activities on farms in Poland and other countries in the European Union. A spatial variation in entrepreneurial farms in the EU in the years 2005, 2007 and 2010 indicated the dominant form of non-agricultural activities.